Newcomer Status as a Protective Factor among Hispanic Migrant Workers for HIV Risk - McCoy, H. Virginia; Shehadeh, Nancy; Rubens, Muni; Navarro, Christi M. (Frontiers in Public Health, 2014)
The HIV rate among U.S. migrant workers is ten times that of the national rate. Due to the highly unstable lifestyle of migrant workers, which places them at heightened vulnerability to sexually transmitted infections (STIs); hence, there is a need to investigate the attitudes and sexual risk factors that may play a protective role in the transmission of HIV in this population. This study examines the association between attitudes and HIV risk behaviors among Hispanic male and female migrant workers (N=255) and their length of stay (shorter length of stay as a protective factor) in Immokalee, Florida. Pearson’s correlation and regression analyses were utilized to analyze the relationship between HIV risk behaviors (intention to use condoms and alcohol use) with length of stay in Immokalee. Longer length of stay positively correlated with number of drinks (p<0.05) and frequency of drinks (p<0.01) and negatively correlated with ethnic identity search (p<0.05). Regression analysis showed that length of stay predicted both behavioral intention to use condoms (p<0.05) and alcohol consumption (p<0.05). The findings suggest that migrant workers who are new to Immokalee may have a higher likelihood of practicing protective HIV risk behaviors and having more favorable attitudes toward risk reduction than long-timers. This study might provide important new evidence on the drivers of multiple concurrent and potential protective factors against risky sexual behaviors among Hispanic migrant workers.